1992
DOI: 10.1111/j.1469-8137.1992.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar uptake and release of inorganic nitrogen compounds in Pinus sylvestris L. and Picea abies (L.) Karst.

Abstract: SUMM.'^RVFoliar uptake and release of inorganic nitrogen compounds were studied by immersing current-year shoots of Scots pine {Pinus syhestris L.) and Norway spruce [Picea ahies (L.) Karst] in either NH^"-or NOg'-rain solutions at different N concentrations. The effects of N form, N concentration and tree species on ion influx and efflux were investigated.Spruce shoots absorbed NH^"^ from the external solution. Uptake apparently occurred by diffusion rather than by H"' or base cation exchange as commonly acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 18 publications
3
32
0
1
Order By: Relevance
“…forest ecosystems (2 to 8%: Boyce et al 1996;up to 5%: Wilson & Tiley 1998). Similarly, as found for aquatic (Touchette & Burkholder 2000) and terrestrial (Wilson 1992, Peuke et al 1998, Ignatova & Dambrine 2000 angiosperms and marine algae (Lotze & Schramm 2000), we found that foliar uptake is generally higher for NH 4 + than for NO 3 -. A linear increase in the uptake rate (Figs.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…forest ecosystems (2 to 8%: Boyce et al 1996;up to 5%: Wilson & Tiley 1998). Similarly, as found for aquatic (Touchette & Burkholder 2000) and terrestrial (Wilson 1992, Peuke et al 1998, Ignatova & Dambrine 2000 angiosperms and marine algae (Lotze & Schramm 2000), we found that foliar uptake is generally higher for NH 4 + than for NO 3 -. A linear increase in the uptake rate (Figs.…”
Section: Discussionmentioning
confidence: 50%
“…Although leaching and the presence of epiphytic macroflora complicates interpretation of throughfall studies (Pearson & Stewardt 1993), it is also evident in terrestrial systems that foliar N-uptake is generally more efficient for NH 4 + than for NO 3 - (Wilson 1992, Peuke et al 1998, Ignatova & Dambrine 2000. In this study, we address the question as to the extent in which foliar uptake of nitrogen contributes to the nutrient demand of halophytic species that grow in the lowest areas of tidal salt marshes.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Deposition of NH 4 + likely stimulated nitrification and related isotope fractionation in the canopy. In tropical and temperate forests, ammonification of organic matter accumulated in the canopy and nitrification at leaf surfaces, respectively, have already been shown (Vance and Nadkarni 1990;Wilson 1992). The high abundance of epiphytes in the canopy and the high litterfall in our research area (Wilcke et al 2002) result in the accumulation of organic matter in the canopy that can be mineralized.…”
Section: Shifts Of δ 15 N Values As Indicator Of N Transformationsmentioning
confidence: 97%
“…Furthermore, the necessity of accurate deposition velocity models [8,9] and the need of scaling factors to relate measurements to forest canopy surfaces complicate this approach. Mineral N compounds in throughfall mainly originate from deposition [19], but the possibility of NH 4 + leaching from leaves has also been shown [28]. In remote or low polluted sites, several authors have found lower NH 4 + and NO 3 -fluxes in throughfall than in rain, suggesting uptake of the N by the canopy.…”
Section: Introductionmentioning
confidence: 99%